AN EMPIRICAL ANALYSIS OF INDIAN INSURANCE SECTOR EMPHASIZING ON STRUCTURAL AND PERFORMANCE INDICATORS - Kansal, Rashmi; Suri, Rachin; Aggarwal, Nipun; Kansal, Renu (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Insurance companies facilitate strategic economic activities in all sectors of an economy such as shipping, aviation, defence, banking, infrastructure, medical, hospitality, manufacturing etc. to mention few as virtually not a single activity is there that is not reliant on insurance depending on the availability in particular political jurisdiction. Consequently, insurance sector performance is systemic to all these sectors and vice versa. The present study delves into analysing the performance of the whole Indian insurance industry including life, non- life, reinsurers, specialized insurers with their foreign branches based on structure, concentration, operation and performance indicators suggested by Abdelrazek Rawan et al., (2005) in the handbook for financial sector assessment which is an outcome of the joint efforts of World Bank and International Monetary Fund. The study takes into account the journey of the Indian insurance industry from 2013-14 to 2023-24 i.e. 11 years period that is a sufficient long duration to predict the trends of future. Relative performance metrics of Indian insurance industry to the world insurance industry is also analysed in the study. The study will help the stakeholders to have the bird eye view of the industry.